What aspects of periods are most bothersome for women reporting heavy menstrual bleeding? Community survey and qualitative study - Warner Pamela; Wyke Sally; Santer Miriam (BMC, 2007)
Abstract Background Heavy menstrual bleeding is a common symptom amongst women of reproductive age, yet questions remain about why some women experience this as a problem while others do not. We investigated the concerns of women who reported heavy menstrual bleeding on questionnaire. Methods A cross-sectional postal survey and qualitative interviews were carried out amongst a community-based sample of women in Lothian, Scotland. 906 women aged 25 to 44 reported heavy or very heavy periods in response to a postal survey of 2833 women registered with 19 general practices. Amongst those who had reported heavy menstrual bleeding, analysis was carried out of responses to the free text questionnaire item, "What bothers you most about your periods?" In addition, 32 of these women participated in qualitative interviews and their accounts were analysed to explore how menstrual symptoms and 'problems' with periods were experienced. Results Even amongst this subgroup of women, selected on the basis of having reported their periods as heavy in the survey, pain was the aspect of their periods that 'most bothered' them, followed by heaviness, mood changes or tiredness, and irregularity or other issues of timing. Interviewees' accounts similarly suggested that a range of menstrual symptoms were problematic and some women did not disentangle which was worst. Judgements of periods as a problem were based on the impact of menstrual symptoms on daily life and this was contingent on social circumstances such as type of paid work and other responsibilities. Although women spoke readily of whether their periods were a problem, there was less clarity in accounts of whether or not menstrual loss was 'heavy'; women said they made judgements based on what was normal for them, degree of difficulty in containing blood loss and pattern of loss. Conclusion Women with heavy periods are bothered by a range of menstrual symptoms and their impact on everyday life. Clinical emphasis should be on clarifying the presenting problem and providing help and advice for this, as well as on excluding serious disease. Sometimes simple approaches, such as help with analgesia, may be all that is required.